Bridging Divides in the 21st Century: Theoretical Rationale for the Special Issue on "Sociality, Intersubjectivity and Social Conflict". Issue 3 (26th July 2022) - Mascolo, Michael F.; Winter, David; Bourne, Dorota
Abstract: Effective social interaction is built upon the foundation of intersubjectivity and sociality. Intersubjectivity consists of the capacity to share, coordinate and mutually incorporate experience between people in social interaction. Sociality operates within the broader context of intersubjectivity. It consists of the process by which one person is able to represent the meaning systems of another person. Sociality is key to understanding how humans enter into, sustain, and otherwise create relationships. It is essential for functional human relating between people, organizations, factions, and ideologies. Many of the problems of the 21 st century – the breakdown of shared meaning systems between and among people – are problems of sociality and can be addressed through the process of cultivating deeper sociality. Sociality thus assumes ethical and political dimensions: we should try and achieve and promote sociality between and among persons. This issue addresses questions about how humans can create shared ways of understanding their worlds, how the development of shared meanings can be derailed, and how we can bridge divides between diverse ways of understanding the world in the 21 st century.